1994
DOI: 10.1029/94jd00263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plumes from biomass burning on atmospheric chemistry over the equatorial and tropical South Atlantic during CITE 3

Abstract: During all eight flights conducted over the equatorial and tropical South Atlantic (27°–35°W, 2°N–11°S; September 9–22, 1989) in the course of the Chemical Instrumentation Test and Evaluation (CITE 3) experiment, we observed haze layers with elevated concentrations of aerosols, O3, CO, and other trace gases related to biomass burning emissions. They occurred at altitudes between 1000 and 5200 m and were usually only some 100–300 m thick. These layers extended horizontally over several 100 km and were marked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
98
4
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 51 publications
12
98
4
2
Order By: Relevance
“…As an illustrative example we show the background data from Flight A10 (blue squares). Regression analysis of the data from altitudes <2 km gives a CN/ CO ratio of 17.2 ± 0.3 cm −3 ppb −1 (r 2 = 0.73, N = 1135), similar to previous results in aged smoke, and consistent with some loss of particles by coagulation and other processes during aging (Andreae et al, 1994;Browell et al, 1996). It is difficult to derive regression slopes from the regional data from the northerly flights, but an overall trend similar to the one indicated for the background on A10 may also apply for these data (blue, green and yellow circles on Fig.…”
Section: Barca-a: Late Dry Seasonsupporting
confidence: 88%
“…As an illustrative example we show the background data from Flight A10 (blue squares). Regression analysis of the data from altitudes <2 km gives a CN/ CO ratio of 17.2 ± 0.3 cm −3 ppb −1 (r 2 = 0.73, N = 1135), similar to previous results in aged smoke, and consistent with some loss of particles by coagulation and other processes during aging (Andreae et al, 1994;Browell et al, 1996). It is difficult to derive regression slopes from the regional data from the northerly flights, but an overall trend similar to the one indicated for the background on A10 may also apply for these data (blue, green and yellow circles on Fig.…”
Section: Barca-a: Late Dry Seasonsupporting
confidence: 88%
“…The modelled increase is not due to an increase in NO y or O 3 that remains nearly constant, but is due to the strong chemical destruction of CO in these runs. Therefore, in the run with chemistry only, an increase in the O 3 /CO slope is the result of a decrease in CO, and not the result of photochemical O 3 production as is often stated (Andreae et al, 1994;Mauzerall et al, 1998). Along the same lines, Chin et al (1994) showed that a decrease in O 3 /CO slopes could be due to the secondary production of CO by hydrocarbon oxidation in a fresh plume, and not just due to chemical destruction or deposition of O 3 .…”
Section: Trace Gas Correlationsmentioning
confidence: 80%
“…Over the Atlantic Ocean, it is likely that dust particles are mixed with marine aerosol (sea salt, organic matter and oxidation products of dimethyl sulfide (Yu et al, 2009)) and biomass-burning aerosols from the Sahel region (Andreae et al, 1994;Formenti et al, 2008;Ansmann et al, 2009). This mixing increases the fine fraction, f , defined as the aerosol fraction with diameter smaller than 1 µm (Kaufmann et al, 2005b).…”
Section: Methodsmentioning
confidence: 99%